State switch control of magnetically suspended flywheel energy storage system in uninterrupted power supply system - Lingbo Zheng; Yili Zheng; Biao Xiang; Xiangbo Xu (Scientific Reports)
Abstract The magnetically suspended flywheel energy storage system (MS-FESS) is an energy storage equipment that accomplishes the bidirectional transfer between electric energy and kinetic energy, and it is widely used as the power conversion unit in the uninterrupted power supply (UPS) system. First, the structure of the FESS-UPS system is introduced, and the working principles at different working states are described. Furthermore, the control strategy of the FESS-UPS is developed, and the switch oscillation of the FESS-UPS system between the charging and discharging states is analyzed. Then, the switch strategy using the angle compensation of the flux linkage is designed to control the FESS-UPS system among different working states, and the peak values of current and voltage at the switch moment are suppressed. Finally, the simulations and experiments are performed to validate the performances of the switch strategy used in the FESS-UPS system, and the results prove that the current/voltage peaks during the switching process are effectively mitigated, so the impact on the power converter caused by the state switch is suppressed. Therefore, the control performance of the UPS using the MS-FESS could be further improved, and the FESS-UPS could realize the fast and safe discharge/charge for the grid source and three-phase loads.